Editorial Vol.26(1) - K.C., Fattah Bahadur; Pathak, Ganesh Prasad; Dhakal, Basanta (Pravaha, 2020)
It is a matter of privilege for us to present Pravaha (A Multidisciplinary Double Blind Peer Reviewed Research Journal) to our valued readers and researchers. This Journal, we believe, will include exposure to some of the most recent trends and emerging issues in modern management and other social science fields. We anticipate that the authors’ research findings, conceptual dimensions, and thought-provoking topics will be extremely useful in our teaching-learning process, as well as for scholars, practitioners, and others in their respective fields. The papers in this Journal are arranged in alphabetical order by the authors’ names. The editorial board is not responsible for the authors’ personal opinions and views expressed in their papers published in this journal. Finally, the editorial board, advisory board, and journal publishing committee owe a debt of gratitude to the paper contributors and campus administration for allowing the Journal to publish this magnificent 26th volume. In the coming days, we will continue our efforts to publish a series of journals.